1992
DOI: 10.2136/sssaj1992.03615995005600030049x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Weathering of a Trioctahedral Mica by the Roots of Ryegrass

Abstract: The weathering of a trioctahedral mica (phlogopite, 2–100‐µm particle size) was investigated in the rhizosphere of ‘Turilo’ Italian ryegrass (Lolium multiflorum Lam.). A special culture vessel made it possible to simulate a one‐dimensional macroscopic rhizosphere by developing a root mat on a polyamide net. This root mat was laid down on a mica‐agar substrate that was cut into slices 0.5 mm thick (parallel to the root mat) after 1, 2, 3, and 4 d of contact. The phlogopite mica was the sole source of both K and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(95 citation statements)
references
References 0 publications
3
91
1
Order By: Relevance
“…The trends in the amounts of mica, chlorite, kaolinite, and 2:1 expandable clays in ECS compared to N-ECM soils support earlier findings (e.g., Hinsinger et al 1992;Kodama et al 1994;Arocena et al 1999). Kaolinite seems to weather faster than mica and chlorite in ECS compared to N-ECM soils.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The trends in the amounts of mica, chlorite, kaolinite, and 2:1 expandable clays in ECS compared to N-ECM soils support earlier findings (e.g., Hinsinger et al 1992;Kodama et al 1994;Arocena et al 1999). Kaolinite seems to weather faster than mica and chlorite in ECS compared to N-ECM soils.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, Robert and Berthelin (1986) showed micrographs of hyphae probing between mica flakes to extract essential K + . In many studies, rootinduced release of interlayer K + was the main reason for the high rates of chemical weathering in rhizosphere zones (Hinsinger et al 1991;Hinsinger et al 1992;Hinsinger and Jaillard 1993;Kodama et al 1994). The formation of vermiculite (a weathering product of mica) is usually caused by the release of K + from mica (Fanning et al 1989) and can take place within a few days (Hinsinger et al 1992).…”
Section: Mineral Composition Of Ecs and N-ecm Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the vermiculitization of mica by plant growth has been reported since the investigation of Mortland et al (1956), it took a long time to have the direct evidence that the vermiculitization of trioctahedral micas can take place within several weeks in the rhizosphere (Hinsinger 1993;Hinsinger et al 1992Leyval et al 1990). Those latter reports were based on pot experiments.…”
Section: Resultsmentioning
confidence: 99%
“…For example, vermiculitization of biotite by plant growth is known (Mortland et al 1956). and Hinsinger et al (1992) demonstrated that such a vermiculitization could occur within a matter of several weeks (even a few days in some cases) in the rhizosphere. Recently, Keller (1990a, 1990b) showed that the mineralogy of the rhizosphere differed from that of the bulk soil in forest soils.…”
Section: Introductionmentioning
confidence: 99%